Efficiency Analysis of Agro-Allied Firms: Implications for Regional Economic Performance in Nigeria - Eyo Bassey Okon (Mustard Journal De Ecobusin, 2024)
Agro-allied industry is a fundamental sector of the Nigeria economic environment, especially in the South-South region that is full of vast agricultural resources. This industry has an enormous impact on the national Gross Domestic Product (GDP), creation of job, and food security. The empirical study to be discussed below looks at how the shipment evaluation management practices affect an operational performance in agro-allied businesses, and at the same time, how the performance of organizations could affect macroeconomic growth. The current research has examined shipment assessment management, but rather little focus has been on the overall impact of this on organizational performance and national building. To fill this gap, the study will take the mixed-methods approach that will entail the incorporation of quantitative survey, qualitative interviews and econometric analysis. The respondent sample was 950 out of 1,494 staff members of six agro-allied companies in the South-South region. Through descriptive statistical processes, including means and percentages, to sum up the demographics variables, inferential studies, such as multiple regression and chi-square tests (p < 0.001) were used to analyse the hypotheses. The results show that the management of shipment evaluation has a positive and statistically significant impact on both the performance and economic growth of the organization, which supports the importance of the management of the agro-allied industry in Nigeria to strengthen the local economy.